Bimbingan Fiqih Taharoh Warga Perumahan Griya Sehati Di Desa Terongtawah Kecamatan Labuapi Lombok Barat - Mappanyompa Mappanyompa; Saprun Saprun; Sahwan Sahwan (Prodi Tadris Matematika-UIN Mataram, 2022)
The importance of cleanliness according to Islam, so that people who clean themselves or seek cleanliness will be loved by Allah SWT. The question of purification and all its intricacies is an important part of knowledge and practice, especially because among the conditions for prayer it has been determined that someone who will pray is obligated to be pure from hadats and also clean the body, clothes and place from najis. The method used in this research is first; the lecture method by listening carefully and noting the important points put forward by the presenter, and the second is direct practice by practicing directly in accordance with the material presented to students.With the service program in the form of studies, Regarding the study of Fiqh Taharoh, it can increase students' knowledge about how to clean properly and correctly in accordance with the guidance of the Prophet Muhammad. in accordance with the guidance in the Book of Fiqh Sunnah in the Taharoh chapter, as well as a form of concern for the Muhammadiyah University of Mataram, especially the Faculty of Islamic Religion towards community problems